2021
DOI: 10.36769/asy.v22i2.194
|View full text |Cite
|
Sign up to set email alerts
|

Peran Akuntabilitas Dan Transparansi Laporan Keuangan Sebagai Variabel Intervening Pada Pengaruh Literasi Terhadap Kepercayaan Muzakki (Studi Persepsi Pada Lazismu Uhamka)

Abstract: Abstrak: Penelitian ini bertujuan untuk mengetahui peran akuntabilitas dan transparansi laporan keuangan sebagai variabel intervening pada pengaruh literasi keuangan terhadap kepercayaan muzakki pada lembaga pengelola zakat. Populasi dari penelitian ini adalah seluruh muzakki pada Lazismu Uhamka. Metode pengumpulan data dengan menggunakan metode kuesioner. Metode analisis data pada penelitian ini yaitu analisis analisis jalur yang diolah dengan program SPSS 23. Hasil penelitian ini membuktikan bahwa literasi b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
1
0
1
Order By: Relevance
“…This finding indicates that budget management transparency during the COVID-19 pandemic is crucial and a prerequisite to promoting service quality in handling COVID-19 as it is a form of government responsibility to the community by providing adequate health services. These results support the research by Istikhomah and Asrori (2019) and Saraswati and Larasati (2021) that transparency can be an intervening variable. However, it was found that budget management accountability could not mediate the relationship between internal control and the quality of services for handling COVID-19.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding indicates that budget management transparency during the COVID-19 pandemic is crucial and a prerequisite to promoting service quality in handling COVID-19 as it is a form of government responsibility to the community by providing adequate health services. These results support the research by Istikhomah and Asrori (2019) and Saraswati and Larasati (2021) that transparency can be an intervening variable. However, it was found that budget management accountability could not mediate the relationship between internal control and the quality of services for handling COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…The higher management accountability will form personnel with good qualifications in providing services (Mokoagow et al, 2013). Thus, accountability also has an intermediary role in the relationship between internal control and service quality performance (Istikhomah & Asrori, 2019;Purwantini & Khikmah, 2014;Saraswati & Larasati, 2021). Based on this explanation, the proposed hypothesis is as follows: H5: The relationship between internal control and service quality is mediated by accountability.…”
Section: Intervening Role Of Accountabilitymentioning
confidence: 99%
“…Hasil penelitian ini mendukung temuan yang dilakukan oleh (Fikri & Najib, 2021) yang mengukapkan bahwasannya akuntabilitas dan minat muzakki memiliki pengaruh yang positif terhadap keputusan muzakki dalam memilih shodaqoh, infaq dan lembaga amil zakat (LAZISNU). Demikian juga (Saraswati & Larasati, 2021) menunjukkan bahwa adanya hubungan positif dan signifikan antara akuntabilitas dengan tingkat kepercayaan Muzakki terhadap Lazismu Uhamka. Oleh karena itu, semakin ditingkatkannya tingkat akuntabilitas Lazismu Uhamka dalam pengelolaan zakat dapat mengakibatkan peningkatan signifikan dalam tingkat kepercayaan Muzakki terhadap lembaga pengelola zakat yang dipilihnya.…”
Section: Pembahasan Pengaruh Akuntabilitas Terhadap Preferensi Muzakk...unclassified